Granuloma Annulare in the Setting of Secukinumab. (1st April 2018) - Clark, Matthew L.; Tobin, Courtney A.; Sutton, Angela; Missall, Tricia Ann
Abstract : Granuloma annulare (GA) is a common benign inflammatory skin condition classically presenting as skin-colored to erythematous dermal papules and annular plaques. Histologically, GA displays a dermal granulomatous infiltrate with palisaded histiocytes surrounding focally altered collagen. The exactly etiology of GA remains unknown, but it has been associated with trauma, various infections, diabetes mellitus, malignancy, thyroid disease, dyslipidemia, and several medications. In 2017, a case of GA developing in a patient treated with the interleukin 17A antagonist secukinumab was reported. Here we report a second case of GA in association with secukinumab use.